PSYCHOLOGICAL DETERMINANTS OF THE DEVELOPMENT OF CREATIVITY IN ADOLESCENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Creativity is realized in various types of the criminal and deviant behavior in almost all the spheres of activity. The interest of psychologists in this phenomenon is growing but the issues of the diagnostics of malevolent creativity, predictors of the realization of original decisions in the behavior, and the evaluation and examination of negative creativity remain unresolved. While the results of the malevolent creativity harm are clear to both the idea generator and the victim, the results of negative creativity cannot always be assessed and examined due to the absence (or the disguise) of the intent to cause harm. The present article aims at reviewing the results of the research of the relationship between creativity and deviance.